URGENSI KEBIJAKAN PEMERINTAH DALAM EDUKASI PENCEGAHAN KEKERASAN SEKSUAL PADA SISWA SEKOLAH DASAR - Sari, Feni Huspita; Andaryani, Sutinah; Hasanah, Ade Uswatun; Solha, Solha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the high number of cases of sexual violence against children in Indonesia, including in elementary schools, as recorded in 2024 data from the Ministry of Women's Empowerment and Child Protection (KemenPPPA) and the Indonesian Child Protection Commission (KPAI). The urgency of child protection, while the perceived suboptimal implementation of existing policies, constitutes a major gap. Therefore, this research focuses on analyzing the urgency of government policies on sexual violence prevention education in elementary schools and identifying barriers to their implementation. Using a descriptive qualitative method with a literature review approach, this study examines regulations (such as Law No. 12/2022 on the Child Protection and Child Protection (TPKS) and Regulation No. 46/2023) and empirical data, analyzed using Mazmanian and Sabatier's implementation theory. The results indicate that although the legal basis exists, its implementation is suboptimal. Key findings reveal obstacles such as a lack of clear technical guidelines, limited teacher capacity, cultural resistance to sexuality education, and weak coordination between institutions. It concludes that policy strengthening through technical regulations, teacher training, social paradigm shifts, and cross-sectoral coordination are essential for effective and sustainable sexual violence prevention education in elementary schools. ABSTRAKPenelitian ini dilatarbelakangi oleh tingginya kasus kekerasan seksual terhadap anak di Indonesia, termasuk di lingkungan sekolah dasar, sebagaimana tercatat dalam data KemenPPPA dan KPAI tahun 2024. Adanya urgensi perlindungan anak namun implementasi kebijakan yang ada dirasa belum optimal menjadi kesenjangan utama. Oleh karena itu, penelitian ini berfokus menganalisis urgensi kebijakan pemerintah dalam edukasi pencegahan kekerasan seksual di sekolah dasar serta mengidentifikasi hambatan implementasinya. Menggunakan metode kualitatif deskriptif dengan pendekatan studi literatur, penelitian ini mengkaji regulasi (seperti UU TPKS No. 12/2022 dan Permendikbudristek No. 46/2023) dan data empiris, dianalisis menggunakan teori implementasi Mazmanian dan Sabatier. Hasil penelitian menunjukkan bahwa meskipun dasar hukum telah ada, implementasinya belum optimal. Temuan utama mengungkap hambatan berupa kurangnya pedoman teknis yang jelas, keterbatasan kapasitas guru, resistensi budaya terhadap pendidikan seksualitas, dan lemahnya koordinasi antar lembaga. Disimpulkan bahwa penguatan kebijakan melalui regulasi teknis, pelatihan guru, perubahan paradigma sosial, dan koordinasi lintas sektor sangat diperlukan agar edukasi pencegahan kekerasan seksual dapat berjalan efektif dan berkelanjutan di sekolah dasar.